基于内容标签的聚合主题内容的方法 (2022)
本发明属于信息技术内容处理领域，尤其是一种基于内容标签的聚合主题内容的方法，针对现有的泛在网络中的信息资源呈爆炸式增长，造成信息资源的重复和过载问题，从而影响用户获取和利用信息资源，并且网络的文章内容参差不齐，大多文章是都是挂羊头卖狗肉，这让追求某个品牌，某个话题内容的用户找不整体高质量的文章的问题，现提出如下方案，其包括以下步骤：S1：基于"内外网内容信息"进行标签聚合主题内容流程处理，然后执行S2；S2：基于"内外网内容信息"储存于分布式发布订阅消息系统中，本发明基于根据不同的扎堆属性、主题来进行内容的聚合，使用户更好的找到相关的内容，也为用户提供更好、更高质量的文章。 The invention belongs to the field of information technology content processing, in particular to a method for aggregating subject contents based on content tags. Aiming at the situations that information resources in an existing ubiquitous network are increased in an explosive mode which causes the problems of repetition and overload of information resources and affects the user's acquiring and utilizing information resources, and a situation that the article content of the network is uneven and most articles sail under false colors, which enables a user pursuing a certain brand and topic content not to be able to find an overall high-quality article, the invention provides the following scheme that the method comprises th